An investigation of performance in working capital management - Samat, Omar; Abdul Nasser, Abu Thahir; Ibrahim, Zin; Abdul Wahid, Emelin; Amiruddin Othman, Ahmad Marzuki (Institut Penyelidikan, Pembangunan dan Pengkomersilan, 2010)
The main purpose of this study is to investigate the performance in working capital management of firm's and the factors that affect the performance. This study evaluates the performance in working capital management of firms' and determines whether factors like size, profitability, and current assets contribute to better performance. In addition, this study also intends to examine the impact of the performance in working capital management on the market prices of the shares. Working capital management plays a vital role in enhancing the economic performance of the corporate sector and thereby enhances the wealth of shareholders. Recently there have been reports about increase in number of corporate failures mainly due to lack of working capital performance and a majority of such firms are identified as small firms. An examination of 252 companies listed on the KLSE over a period of five years reveals that the size in terms of fixed assets and profitability of the firm influences the performance of working capital management positively. This study also provides evidence that there is a linear positive relationship between the performance in working capital management and the market prices of the shares. This study, for the first time, treated performance in working capital management as dependent variable and explained its significant relationship to the size of the firm. The findings of this study provide a useful insight for the researchers and corporate finance managers.